Exploring the mediating role of PsyCap in the relationship between orientation training and work engagement: the perspective of COR and SRT theories - Song, Zibin; Zhang, Houchen; Li, Jie (Frontiers in Psychology, 2023)
In the domain of organizational socialization, a new research paradigm and trend concerns work engagement path way to studying newcomer assimilation through the lens of socialization resource theory (SRT). Drawing on theories of SRT and COR (conservation of resources), the present study develops and validates an integrative model, in which the effect of orientation training on work engagement involves the mediator of PsyCap and moderators of leader-member exchange (LMX) and education. SmartPLS 3.0 was used to analyze the data with 567 respondents with 5,000 bootstraps from 3- to 5-star hotels in Mainland China. The empirical results indicate that newcomers’ PsyCap fully mediates the relationship between orientation training and work engagement. They also suggest that education and LMX, respectively, moderate the effects of orientation training on PsyCap and work engagement. Theoretical and practical implications of these findings are drawn in the context of organizational socialization and human resources development.